Expert System For Phobia Diagnosis Using Certainty Factor (CF) Method - Bimantara, I Made Satria; Astuti, Luh Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2021)
A phobia is an excessive fear of a certain situation or object that can hinder the life of the sufferer. Phobias that are not immediately treated in individuals can lead to a state of frustration and even depression and the worst situation is the feeling of wanting to commit suicide. The earlier it is known that a person's phobic disorder is experienced, the faster treatment can be done by an expert. Expert systems can be used to diagnose a person's phobia and replace the role of an expert through a computer program. The expert system developed can diagnose nine phobias using 84 symptoms which are divided into three types of symptoms. Knowledge about phobias was obtained from a health online site in partnership with the Ministry of Health of the Republic of Indonesia. Certainty Factor (CF) method is used to overcome uncertainty in determining a disease based on its symptoms that usually occur in expert systems. The expert system is implemented based on a website using the PHP programming language and MySQL database. The CF method can be used to determine the percentage of a person's phobia based on symptoms by taking into account the weights of experts and users. System testing using Blackbox Testing shows that all the features that have been implemented in the expert system can function properly.